Cardiovascular risk assessment in periodontitis patients and controls using the European Systematic COronary Risk Evaluation (SCORE) model. A pilot study. - Kosho, Madeline X. F.; Verhelst, Alexander R. E.; Teeuw, Wijnand J.; Gerdes, Victor E. A.; Loos, Bruno G. (Frontiers in Physiology, 2023)
Aim: To investigate the use of the European SCORE model in a dental setting by exploring the frequency of a ‘high’ and ‘very high’ 10-year CVD mortality risk in patients with and without periodontitis. The secondary aim was to investigate the association of SCORE with various periodontitis parameters adjusting for remaining potential confounders. Material and methods: In this study, we recruited periodontitis patients and non-periodontitis controls, all aged ≥40 years. We determined the 10-year CVD mortality risk per individual with the European Systematic Coronary Risk Evaluation (SCORE) model by using certain patient characteristics and biochemical analyses from blood by finger stick sampling. Results: In total, 105 periodontitis patients (61 localized, 44 generalized stage III/IV) and 88 non-periodontitis controls were included (mean age: 54.4 years). The frequency of a ‘high’ and ‘very high’ 10-year CVD mortality risk was 43.8% in all periodontitis patients and 30.7% in controls (p = .061). In total, 29.5% generalized periodontitis patients had a ‘very high’ 10-year CVD mortality risk, compared to 16.4% in localized periodontitis patients and 9.1% in controls (p = .003). After adjustment for potential confounders, the total periodontitis group (OR 3.31; 95% CI 1.35–8.13), generalized periodontitis group (OR 5.32; 95% CI 1.90–14.90), lower number of teeth (OR .83; 95% CI .73–1.00) and higher number of teeth with radiographic bone loss ≥33% (OR 1.06; 95% CI 1.00–1.12) were associated with a “very high” SCORE category. In addition, various biochemical risk markers for CVD were more frequently elevated in periodontitis compared to controls (e.g., total cholesterol, triglycerides, C-reactive protein). Conclusion: The periodontitis group as well as the control group had a sizable frequency of a ‘high’ and ‘very high’ 10-year CVD mortality risk. The presence and extent of periodontitis, lower number of teeth and higher number of teeth with bone loss ≥33% are significant risk indicators for a ‘very high’ 10-year CVD mortality risk. Therefore, SCORE in a dental setting can be a very useful tool to employ for primary and secondary prevention of CVD, especially among the dental attenders who have periodontitis.